CLINICAL PICTURE OF ENDOMETRIOSIS IN ADOLESCENTS (Conference Zone, 2023)
Endometriosis is a chronic gynecological disease in which there is growth and development of tissue similar to the endometrium outside the uterine cavity, causing pain and infertility, thereby reducing the quality of life of women of reproductive age [1]. Unfortunately, this disease occurs even in adolescents, and this figure reaches up to 49-75% [2]. Endometriosis is the most common cause of secondary dysmenorrhea in adolescent girls and is characterized by pain despite treatment with non-steroidal anti-inflammatory and hormonal drugs [3].